Konsepsi Pengembangan Masyarakat Melalui Sekolah Inklusif Bagi Penyandang Down Syndrome - Fadri, Zainal (Fakultas Dakwah dan Ilmu Komunikasi, 2021)
The concept of community development is a necessity in the field of special education. Special education is a challenge in itself for implementers of social welfare programs. This study aims to propose a community development model in providing education for people with Down syndrome so that the entire community can enjoy educational development programs. The method used in this research is descriptive qualitative to reveal facts and contribute thoughts in community development in the field of education. Data mining was carried out with a literacy approach and policy considerations derived by the government in order to obtain a critical analysis and recommendations for the concept of education for people with Down syndrome. The results of this study indicate several recommendations that can be applied to implement community development programs in the field of education and applications in the form of inclusive schools in order to create an equitable and equitable education scheme.